Framing of Sea Level Rise in News Headlines: A Study of The Guardian and The New York Times - Mohar, Tjaša; Prajnč Kacijan, Nastja; Hempkin, Kirsten; Leva, Bernarda; Onič, Tomaž; Majcenovič Kline, Barbara; Hazemali, David; Plemenitaš, Katja (Komuniciranje okoljske krize, 2025)
The deepening of the environmental crisis brings an increased need for clear and targeted communication about environmental issues, leading to greater environmental awareness and encouraging the necessary changes in people’s behaviour. The way the media frames reports on environmental issues, such as climate change, plays a crucial role in the efficient communication of these issues. This paper examines how sea level rise was reported in the digital editions of The Guardian and The New York Times in 2022, utilizing framing theory – a theory that is used in textual linguistics to study texts on socially important topics in public discourse. The study identifies the predominant generic frames in the headlines and subheads of these articles, which are the key framing locations. A comparative analysis also reveals differences in the framing of sea level rise in the two newspapers.